Thermal properties of starch from transgenic isolines of wheat differing in starch surface components - Nath de Oliveira, Daniela (Kansas State University, 2010)
Endosperm texture is an important characteristic in determining wheat processing and end-use. The presence of puroindoline proteins on the starch surface is the biochemical marker for wheat hardness. Near-isogenic samples over expressing puroindolines have been used to assess the effect of wheat hardness on final product characteristics. The objective of this study was to determine differences among starch isolated from near-isogenic samples and to investigate the role starch surface components play in pasting. The use of near-isogenic samples over expressing puroindolines combined with the use of two methods of starch isolation (batter and dough) was an effective means to create samples with varied amounts of surface components. Starch thermal properties were characterized and surface proteins and lipids were quantified. Starch isolated from hard wheat cultivars presented more similarities with starch isolated from its soft near-isogenic line when a dough method was used than when a batter method was used. Starch from soft experimental lines isolated using a batter method showed increased MVA peak viscosity, breakdown and swelling power. Increased levels of LysoPC in starch isolated from hard wheat cultivars or soft experimental lines by dough method could have complexed with amylose and restricted granule swelling. Thereby, decreasing peak viscosity, breakdown and swelling power.
Keywords: near-isogenic; puroindoline; polar lipids; wheat starch; gelatinization; swelling power; Agriculture, Food Science and Technology (0359)